Managements of Facilities and Infrastructure in Enhancing the Interest of Prospective Student at Madrasah Tsanawiyah Asy-Syarifah Demak, Central Java - Amin, Muhammad Safiul; Husin, Saddam (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to describe the implementation of infrastructure management in enhancing the enthusiasm of prospective students at Madrasah Tsanawiyah Asy-Syarifah Demak, Central Java. This study employs a qualitative research approach with a focus on the processes of planning, procurement, maintenance, and supervision of infrastructure. The research found that effective implementation of infrastructure management includes: Planning involves comprehensive needs analysis, identification of the required budget, and establishment of procurement priority scales. Procurement conducted through purchasing, accepting grants, leasing, borrowing, and refurbishing. Maintenance includes forming a maintenance team, routine inventory recording, and evaluating the maintenance of infrastructure. This involves reporting the results of supervision to the school principal and foundation, as well as periodic reporting. The data analysis results indicate that awareness and motivation among prospective students increase when school infrastructure is available and well-maintained. Therefore, comprehensive infrastructure management is crucial in enhancing the enthusiasm and motivation of prospective students so that they are prepared, interested, and motivated to learn at Madrasah Tsanawiyah Asy-Syarifah Demak, Central Java.